Emission pattern of higher alcohol-biodiesel blends in compression ignition engine. (2021) - Devaraj, A.; Nagappan, M.; Yogaraj, D.
Abstract: Present study investigate the emission pattern of compression ignition engine using Jatropha (J100), Deconal blends with jatropha (JB90D10, JB80D20) and compared with conventional Diesel (D100). Emission parameters such as hydrocarbon (HC), Carbon Monoxide (CO), Nitrogen Oxides (NOx) was measured using gas analyser at various load conditions. Without any additives deconal can be directly added with biodiesel. Engine is quiet smooth in operation and no damage is found in engine parts. Jatropha biodiesel results lower level of carbon monoxide and hydrocarbon with increase in NOx emission. Appending Deconal blends with JB100 shows reduction compared with diesel at all loads.